PENGARUH PENGGUNAAN MODEL SAVI TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI PADA SISWA KELAS XI SMA NEGERI 10 KABUPATEN TEBO - Erlina Zahar; Muhd. Marwan Destian (Universitas Batanghari, 2020)
The purpose of this research is to describe the influence of using Savi learning model on writing explanatory text for class XI students of SMA Negeri 10 Kabupaten Tebo. The method used in this research is quasy-experimental. In this research, 2 classes were used, namely the XI IPS 2 class control class which consists of 18 students and the XI IPS 1 the experimental class which also consists of 18 students. The requirements test that is carried out is the normality test and the homogeneity test. The results of the normality test for the experimental class are 0.24> 0.05 and for the control class are 0.78> 0.05. It means that the data are normal. The homogeneity test results is 0.661> 0.05 which means that the data are homogeneous. Thus the hypothesis can be tested. Hypothesis testing is done using the t-test formula. The results of this research indicate that the value of t = 3.633 is higher than t table = 2.024. It can be concluded that there is an influence of using the Savi model on the learning outcomes of writing explanatory text for class XI students of SMA Negeri 10 Kabupaten Regency. The average value of the experimental class is 79.72, which was higher than the control class value of 60.56.